2021
DOI: 10.1038/s41598-021-92765-0
|View full text |Cite
|
Sign up to set email alerts
|

Interdigital concept in photonic sensors based on an array of lossy mode resonances

Abstract: Multi-parameter detection is key in the domain of sensors. Here it is demonstrated that an indium tin oxide (ITO) nanocoating can be used to generate multiple lossy mode resonances (LMRs) in the optical spectrum. To achieve this, a nanocoating with a gradient in thickness is generated on the surface of a planar waveguide, permitting broadening of the LMR because the position of an LMR in the optical spectrum is directly related to the nanocoating thickness. The nanocoating with a gradient in thickness contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This is the case of what has been called interdigital photonic sensors developed by I. Dominguez et al, where up to 9 independent resonances have been reported on the same substrate [35]. If each of these 9 strips are biofunctionalized differently (see fig.…”
Section: Some Advances In the Lmr Technologymentioning
confidence: 96%
“…This is the case of what has been called interdigital photonic sensors developed by I. Dominguez et al, where up to 9 independent resonances have been reported on the same substrate [35]. If each of these 9 strips are biofunctionalized differently (see fig.…”
Section: Some Advances In the Lmr Technologymentioning
confidence: 96%
“…Transparent conducting oxide thin films and particularly indium-tin-oxide (ITO) films find their applications in integrated touch sensors for flexible OLED displays, photovoltaic cells, LCDs, optical fiber sensor, gas sensing, analysis of ionized media and opto-electrochemical label free biosensors [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. ITO films are transparent, conducting and chemically stable and can be used for integrated-optic sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…LMRs can be generated on this type of substrate and easily polarized by using a linear polarizer. It has been demonstrated that using coverslips, instead of other glass planar substrates such as slides, allows the generation of LMRs with better characteristics such as resonance depth, a more directive coupling, and even the possibility of multiparameter detection [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%